(untitled) (Bangladesh Journal of Agricultural Research, 2008)
Legumes are important constituents of Bangladeshi diet and provide a considerable portion of dietary proteins, minerals, and vitamins. The ready to eat soup powder prepared from legume and vegetables in the laboratory can provide an improved nutritional status. Incorporating processed rice, corn, and processed wheat flour as the starch source, three different samples of soup powder were prepared. Protein source was derived from legumes and vegetable paste was used as a mineral source. All these three developed formulations have a protein value ranging from 19.00 to 19.40% and calorie content 347 to 353 Kcal/100g (Table 2). Sensory evaluation of the products revealed a reasonable acceptance of the sample prepared from wheat flour. The selected soup powder contains 19.40 percent protein and 350 Kcal of energy per 100g. Commercially available soup powder was compared with all samples in the light of its nutritional values. Protein and energy content of the selected sample is comparable with the commercial one, which contain only 7.77 percent protein and 297 Kcal energy per 100 g. Prepared soup powder is also a good source of carbohydrate and minerals, mainly iron, calcium & phosphorus. Storage study was conducted to determine the shelf life of the developed food product. Statistical analysis shows that there is no significant difference during the storage of the selected soup powder for six months DOI: http://dx.doi.org/10.3329/bjar.v32i3.547 Bangladesh J. Agril. Res. 32(3) : 451-459, September 2007